Prediction greenhouse gas emissions from road freight flow in South Korea for sustainable transportation planning - Hoseok Nam; Jihye Byun; Hyungseok Nam (Heliyon)
Road freight modeling was conducted to project freight flow and greenhouse gas (GHG) emissions in 16 administrative regions of South Korea through 2050. Origin-destination matrices were constructed using a gravity model for each region. The modeling covered seven product categories for both inter-regional and intra-regional freight transportation and was validated using 2017 data. The total future freight flow is projected to increase from 1399 million tons in 2019 to 1701 million tons by 2035. However, after peaking in 2035, it is expected to decline to 1618 million tons by 2050, indicating that population decline will impact product demand, causing a reduction in freight flow despite continued economic growth. GHG emissions are projected to slightly decrease from 19.0 million kgCO2eq. in 2025 to 18.6 million kgCO2eq. in 2035, followed by a steeper reduction to 15.5 million kgCO2eq. by 2050. This decline is attributed to both population decrease and long-term reductions in emission factors. Changes in freight flow between 2019 and 2050 are expected to be more pronounced within five regions in the capital and extended capital areas, which will account for approximately 50.3 % of the total freight flow due to population concentration. As a result, these five regions contribute 26.5 % of the total GHG reduction potential. The minimum economic growth rates required to maintain the same freight volume as in 2035 are estimated at 5 % for 2040, 13 % for 2045, and 26 % for 2050.